An Energy Meter Reader with Load Control Capacity and Secure Switching Using a Password Based Relay Circuit - Edward, Ofoegbu Osita (2014 Annual Global Online Conference on Information and Computer Technology, 2014)
Energy conservation and its efficient utilization has been a subject of discourse amongst numerous stakeholders since the industrial age. Advancements in information technology tools thus provides a solution to automating the process of electricity metering as well as remote load control alternatives. This paper thus presents an energy meter reader implemented with a microcontroller based logic methodology fused with a building automation system to implement remote load control by home owners using SMS from a GSM phone. A password based relay circuit was incorporated to ensure secure switching by the user. The system when deployed can enable users query and set energy consumption rates remotely so as to reduce the cost on final consumers as well as conserve energy.